2010
DOI: 10.1364/oe.19.000141
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz imaging and spectroscopy of large-area single-layer graphene

Abstract: We demonstrate terahertz (THz) imaging and spectroscopy of a 15 × 15-mm2 single-layer graphene film on Si using broadband THz pulses. The THz images clearly map out the THz carrier dynamics of the graphene-on-Si sample, allowing us to measure sheet conductivity with sub-mm resolution without fabricating electrodes. The THz carrier dynamics are dominated by intraband transitions and the THz-induced electron motion is characterized by a flat spectral response. A theoretical analysis based on the Fresnel coeffici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 23 publications
6
85
1
1
Order By: Relevance
“…This result agrees very well with our previous work (σ s 02.04×10 −3 Ω −1 ), where we used a Si: Bolometer to measure the transmitted THz power through the sample [14].…”
Section: Terahertz Time-domain Spectroscopy Of Graphene-on-sisupporting
confidence: 92%
See 1 more Smart Citation
“…This result agrees very well with our previous work (σ s 02.04×10 −3 Ω −1 ), where we used a Si: Bolometer to measure the transmitted THz power through the sample [14].…”
Section: Terahertz Time-domain Spectroscopy Of Graphene-on-sisupporting
confidence: 92%
“…THz spectroscopy of epitaxial graphene on SiC has shown that the carrier scattering time is estimated as~2 fs [13]. It was recently demonstrated that THz imaging and spectroscopy of a large-area, single-layer graphene film clearly mapped out the THz carrier dynamics of the graphene and measured the sheet conductivity with sub-mm resolution without fabricating electrodes [14].…”
mentioning
confidence: 99%
“…In addition, most of the far-IR work to date has only measured the relative change in transparency/reflectivity/conductivity, and not the absolute value, which is more difficult to ascertain. A complementary time-domain (sub-ps pulse) technique has demonstrated sheet conductivity of single-layer graphene of up to 30 e 2 /4ħ from 0.5-2 THz at room temperature [6], and low temperatures [7]. These time-domain techniques provide lower spectral resolution than the continuous wave (CW) frequencydomain techniques presented here, but in principle yield the same physical information.…”
Section: Introductionmentioning
confidence: 87%
“…In the THz regime, however, a Drude absorption peak is expected due to free carriers [40]. This prediction has been tested on both CVD and epitaxially grown graphene, using both THz TDS and far-IR Fourier transform interferometer (far-IR FTIR) spectroscopy [40][41][42][43].…”
Section: Terahertz Transmission and Equilibrium Conductivity Of Graphenementioning
confidence: 99%
“…In addition to these FTIR measurements, Tomaino et al utilised THz time domain spectroscopy to map the carrier dynamics of a large area CVD sample on a silicon substrate with > 90% monolayer coverage [43]. THz transmission through the sheet as a function of position was measured, and used to deduce the local sheet conductivity, σ s .…”
Section: Terahertz Transmission and Equilibrium Conductivity Of Graphenementioning
confidence: 99%